2018
DOI: 10.1007/s00405-018-5068-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anatomic origin of primary squamous cell carcinomas of the nasal cavity and ethmoidal sinus on clinical outcome

Abstract: PurposeSince squamous cell carcinomas (SCCs) of the nasoethmoidal complex are rare and aggressive malignancies, the purpose of this study was to evaluate whether anatomic subsites of SCCs of the nasal cavity and ethmoid sinuses affect clinical outcome.MethodsWe retrospectively analyzed data from 47 patients with primary SCCs of the nasal cavity and ethmoid sinuses who were treated at the Department of Otorhinolaryngology, Head and Neck Surgery, Medical University of Vienna, between 1993 and 2018. The impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Secondly, the decreased quantity of performed ENDs and thirdly the retrospective study-design including a low number of patients represent a drawback of this study. In contrast, considering the current literature regarding T1 and T2 sinonasal SCCs, published cases are ranging from 10 to 35 cases that proofs that our cohort is representative [6,9,11,17,19,30,32]. Additionally, sinonasal tumors are known to be very rare tumors with an incidence of 5.6 cases per million [30].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Secondly, the decreased quantity of performed ENDs and thirdly the retrospective study-design including a low number of patients represent a drawback of this study. In contrast, considering the current literature regarding T1 and T2 sinonasal SCCs, published cases are ranging from 10 to 35 cases that proofs that our cohort is representative [6,9,11,17,19,30,32]. Additionally, sinonasal tumors are known to be very rare tumors with an incidence of 5.6 cases per million [30].…”
Section: Discussionmentioning
confidence: 84%
“…A more recent metaanalysis (n = 1283) has reported nodal involvement in 14.2% (range, 4-27%) of cases depending on tumor site and extension [2]. We have recently found remarkable differences regarding clinical behavior based on anatomic subsite, such as lymph node involvement and subsequently outcome in patients with SCCs of the nasoethmoidal complex [9]. Nonetheless, elective nodal treatment has no value in the current treatment of sinonasal SCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Although nasoethmoidal tumours located within the nasal cavity may be detected at earlier stages making longer survival more likely, other factors also contribute to survival. For instance, it has been recently found that tumour location at the nasal septum, where early detection is common, is a negative prognostic factor due to early neck involvement 9 . Our finding that, for tumours of the nasoethmoidal complex, extension beyond OL represents a negative prognostic factor is of interest as OL has not been directly included in the staging of tumours of the nasoethmoidal complex.…”
Section: Discussionmentioning
confidence: 86%
“…Squamous cell carcinomas (SCCs) of the sinuses represent a rare and aggressive malignancy. Risk factors associated with SCCs are smoking, human papilloma virus (HPV) infection, and occupational exposure to nickel and welding fumes [1]. The standard of care is surgery, when amenable, followed by radiotherapy [2].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation can be very unspecific, often times it is misdiagnosed with inflammatory sinus disease, which delays treatment. Symptoms reported by patients are epistaxis, pain, swelling, foreign body sensation, and nasal obstruction, among others [1]. This disease is usually diagnosed late, when some vital structures are compromised, making the treatment more challenging.…”
Section: Introductionmentioning
confidence: 99%